2015
DOI: 10.1177/0022427815587761
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Surveillance Banner in an Attacked Computer System

Abstract: Objectives: Test whether the presence of a surveillance message on an attacked computer system influences system trespassers’ active engagement with the compromised system (i.e., entering computer commands). The hypothesized restrictive deterrent effect is tested both in the context of a first system trespassing incident and in the progression of repeated trespassing incidents in an attacked computer system. Methods: We designed a randomized controlled trial and deployed a series of virtual target computers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Another option based on situational crime prevention models would be to provide easy access to positive alternatives in the event of identifying a vulnerability to remove offender excuses for not reporting. For example, just as studies that use banners to inform potential system trespassers about the negative consequences of system trespassing (Maimon et al 2014;Testa et al 2017;Wilson et al 2015), clear and eye-catching information about a website's CVD policy could help a person understand there are rules and guidelines to report a vulnerability. Additionally, it would be advisable to keep the threshold for reporting low, to make sure that the potential costs of CVD are as low as possible.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another option based on situational crime prevention models would be to provide easy access to positive alternatives in the event of identifying a vulnerability to remove offender excuses for not reporting. For example, just as studies that use banners to inform potential system trespassers about the negative consequences of system trespassing (Maimon et al 2014;Testa et al 2017;Wilson et al 2015), clear and eye-catching information about a website's CVD policy could help a person understand there are rules and guidelines to report a vulnerability. Additionally, it would be advisable to keep the threshold for reporting low, to make sure that the potential costs of CVD are as low as possible.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A growing body of research has highlighted the importance of risk perception in the decision making of offenders (Cherbonneau and Copes, 2006;Beauregard and Bouchard, 2010;Gallupe et al, 2011;Jacobs and Cherbonneau, 2014Maimon et al, 2014;Wilson et al, 2015;Moeller et al, 2016). Perception of risk (subjective risk of punishment) is an extension of actual risk (objective risk of punishment).…”
Section: Perception Of Riskmentioning
confidence: 99%
“…Since Gibbs (1975, p. 33) introduced the concept of restrictive deterrence, it has been substantively explored on samples of drug offenders (Jacobs, 1993(Jacobs, , 1996a. Originally based on research concerning drug offenders, restrictive deterrence was also gradually extended to a broader range of criminals, such as auto thieves, sex workers, sexual offenders, and computer hackers, among others (Jacobs and Miller, 1998;Cherbonneau and Copes, 2006;Beauregard and Bouchard, 2010;Gallupe et al, 2011;Jacobs and Cherbonneau, 2014;Maimon et al, 2014;Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have examined opportunity factors and cybercrime offending with varying results. For one, Maimon et al (2014) investigated the influence of a warning banner on the frequency and duration of hacking incidents directed at computer systems online (see also Wilson et al, 2015). The study found that while the use of warning banners did not lead to an immediate discontinuation of the hacking incident, it reduced the duration of each hacking incident.…”
Section: Understanding Computer Hacking and Hacker Behaviorsmentioning
confidence: 99%